Acute and Repeated Dose 28-day Oral Toxicity Studies of Ich Tri Hadiphar Capsules - Thi Lien, Nguyen; Hang, Nguyen Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Abstract:   Ich tri Hadiphar capsules used for dementia treatment were evaluated for acute and repeated dose toxicities in mice and rabbits, respectively. The acute toxicity results indicated that LD 50 of Ich tri Hadiphar capsules in mice according to the method of Behrens is greater than 30 g/kg body weight. In the repeated dose toxicity study, rabbits were administrated Ich tri Hadiphar with doses of 186.5 and 560.0 mg/kg/day for 28 days (equivalent to the dose used on humans and the dose of 3 times more than one used on humans). Blood samples were taken on day 0, day 14, and day 28 of the experiment for hematological and biochemical analysis. Liver and kidney samples were taken on day 28 for histopathological determinations. The repeated dose toxicity results revealed that there were no significant differences in hematological and serum biochemical values between control and treatment animals. Furthermore, no histopathological changes in the liver and kidney of rabbits treated with Ich tri Hadiphar capsules were observed. Keywords: A cute toxicity, repeated dose toxicity, Ich tri Hadiphar.